2012
DOI: 10.4236/me.2012.32030
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Quality, Economic Growth and Fluctuations of Oil Prices in Oil Dependent Countries: A Panel Cointegration Approach

Abstract: The principle aim of this investigation is the study of fluctuations of oil prices impacts on economic growth of oil-dependent countries with respect to institutional quality. For this purpose we use panel cointegration methodology and error-correction model for 32 oil abundant countries covering the period 1975-2010. The result implies that fluctuations of oil prices impact on economic growth of countries depend on institutional quality index so that the impact of fluctuation is avoided by countries with suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Similarly, Ciscar et al [39] analyses the potential effects of oil price on European Union (EU) using the General Equilibrium model and finds a negative relationship between oil price and economic activity. Similar results were found by Anoruo and Elike [40] based on oil importing African countries; and Keikha et al [41] based on oil dependent countries.…”
Section: B Empirical Literaturesupporting
confidence: 89%
See 3 more Smart Citations
“…Similarly, Ciscar et al [39] analyses the potential effects of oil price on European Union (EU) using the General Equilibrium model and finds a negative relationship between oil price and economic activity. Similar results were found by Anoruo and Elike [40] based on oil importing African countries; and Keikha et al [41] based on oil dependent countries.…”
Section: B Empirical Literaturesupporting
confidence: 89%
“…Hakan et al [66] revealed that oil price is statistically significant to economic growth of Algeria Tunisia, Jordan, Kuwait, and Iran. Similar results were found by Elike and Anoruo [64], on their study of the effect of oil price on oil importing African countries and Keikha et al [41] on their study of the effect of oil price on selected oil dependent countries.…”
Section: B Empirical Literaturesupporting
confidence: 88%
See 2 more Smart Citations
“…No support was obtained for the hypothesized environmental Kuznets curve. Granger-causality results confirm a unidirectional causality running from economic growth to carbon emissions Keikha et al (2012) Oil prices fluctuations -economic growth -institutional quality, 32 oil rich countries, 1975-2010…”
Section: Multivariate Vector Error Correction (Vecm) Frameworkmentioning
confidence: 76%